CORONECTOMY IN LOWER THIRD MOLAR AS AN ALTERNATIVE TECHNIQUE FOR PRESERVATION OF THE INFERIOR ALVEOLAR NERVE - Marques, Ariele Cardoso Marques; Loiola dos Santos, Yrla; Mello Lócio, João Paulo (Health and Society, 2023)
One of the procedures frequently performed by dentists is the removal of lower third molars. These teeth are commonly impacted and have an intimate relationship with the inferior alveolar nerve (IAN). The use of the coronectomy or intentional partial odontectomy technique is indicated in cases where the lower third molars have roots close to or associated with the IAN in order to avoid iatrogenic injuries. The technique consists of extracting the dental crown and cervical portion of the root, while the apical remainder is left in its natural place. This work aimed to describe coronectomy, including its procedural technique, advantages, indications and contraindications, as well as to understand the postoperative phenomena associated with lower third molars in close contact with the IAN. Nineteen articles from the last thirteen years were selected from the databases PubMed, Scielo, Google Scholar and CAPES journals with an emphasis on systematic reviews, published in English and Portuguese. Therefore, it is concluded that coronectomy is considered a satisfactory, safe and effective technique to be used in clinical practice, as long as the dentist knows how to indicate it appropriately, reporting its indications, contraindications and limitations.